Analisis Faktor Loyalitas Konsumen Terhadap Provider Telepon Seluler Telkomsel Studi Pada Mahasiswa Teknik Universitas Muhammadiyah Surakarta) - Bachtiar, Yngwied Kusumastuti; , Dr. Suranto, MM (2016)
This study aims to determine the factors that shape consumer loyalty to the cellular phone providers Telkomsel. The variables in this study amounted to 5, which is divided into 21 sub-variables. Of the 21 variables are extracted into a dominant factor. Besides this research also to find out the names of the factors that have been formed.The method in this study is exploratory factor analysis (EFA) and Confirmatory Factor Analysis (CFA). The analytical tool used was SPSS 17.0. The number in this study as many as 60 data. Methods of data collection using three methods, namely interviews, observation and questionnaires. There are five variables that determined that price, the quality of the signal, amenities / features, recommendations and promos. Of the five variables are divided into 21 sub-item questions or variables.The results of this study showed that of the five variables that have been divided into 21 sub-variable predetermined extracted into six important factors. 6 of these factors later in the appropriate interpretation of the variables that are inside. The name of these factors is a package of internet and telephone sms bonus, the price of pulses and the prime, sms telephone tariff, recommendations and promo connections and references. Then six of these factors in the validation using the CFA test. CFA test obtained from the distribution of the variable to 7 factors. Keywords: Loyalty, Connection, Features, Provider, Sub Variables, Variable